Mantenimiento predictivo, correctivo y deductivo de los transformadores de distribución en el Laboratorio de CNEL EP Los Ríos - Moreira Posligua, Darwin Stalin (2021)
Within the Maintenance of a Transformer, we know that they are those that are responsible for reducing or expanding the current from high voltage (AT) to low voltage (BT), these are found in substations in the distribution networks, generation plants, shopping centers, large buildings, hospitals, industries, mining, oil exploitation, urban areas, thermoelectric plants, etc. The same that can present the failures caused by humidity, water, oxygen, heat, external contamination, vibrations, surges also by phenomena of electrical, electrodynamic, electromagnetic, dielectric, thermal or mechanical origin. The same that can be catastrophic so the implementation of systematic preventive, predictive and corrective maintenance programs is recommended that allows us to make changes or corrections in some physical part of the transformer that occurred due to some failures caused by some origin to which we give correction and solution to damage by lengthening its useful life for proper operation. In which we have highly trained and active personnel to carry out said maintenance in order to offer and make known that maintenance is very important in the field of transformers and to be able to do them consecutively (semester) carrying a deductive diagnosis and then be able to make it corrective.